2020
DOI: 10.9779/pauefd.515080
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Bilimsel Sorgulama Görüşleri: Cinsiyet, Sınıf Düzeyi ve Okul Türü Değişkenlerinin İncelenmesi

Abstract: Bilimsel sorgulama (BS), bilim okuryazarı öğrencilerin hedefine ulaşmada en önemli bileşenlerden birisidir. Öğretim programında 'anlayış' ve 'beceri' olarak farklı ifade edilmiş olsa da BS hakkında bilinçli düzeyde görüşlere sahip olan öğrencilerin bu konudaki becerilerinin de daha fazla gelişeceği açıktır. Sorgulama becerilerinin ve anlayışının geliştirilmesi, sorgulamaya dayalı stratejilerin ve sınıf içi uygulamalarının dikkatli bir şekilde planlanmasını ve uygulanmasını gerektirir. Ancak, sorgulamaya dayalı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
2
1
0
2
Order By: Relevance
“…Further, they are inadequate to develop students' scientific understanding and research skills. Similar findings have been reported in other studies (Doğan et al, 2020;Et, 2023;Karaaslan & Ayaş, 2017;Lederman et al, 2014;Schwartz et al, 2004), which have concluded that many concepts such as scientific thinking, hypothesizing, and generating scientific knowledge are not adequately taught. Therefore, the number of activities in science textbooks should be increased and these activities should be designed to support the development of students' scientific understanding and encourage them to conduct research.…”
Section: Discussionsupporting
confidence: 90%
“…Further, they are inadequate to develop students' scientific understanding and research skills. Similar findings have been reported in other studies (Doğan et al, 2020;Et, 2023;Karaaslan & Ayaş, 2017;Lederman et al, 2014;Schwartz et al, 2004), which have concluded that many concepts such as scientific thinking, hypothesizing, and generating scientific knowledge are not adequately taught. Therefore, the number of activities in science textbooks should be increased and these activities should be designed to support the development of students' scientific understanding and encourage them to conduct research.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results, there was a significant difference between 5th and 6th grades and the 7th and 8th grades in favor of 5th and 6th grades in terms of grade variable (p<.05), the inquiry skills decreased as the grade level increased was observed. In line with the results of this research, Doğan et al (2020), İnel Ekici (2017 and Martin (2003) reported that students' inquiry skills and perception skills decreased as they moved up to the higher classes. The high level of inquiry skills at the 5th grade may be due to the more advanced curiosity of the students.…”
Section: Extended Abstractsupporting
confidence: 84%
“…Bu meraklarını ve sorgulamalarını ilerleyen yaşlarda kaybetmemeleri önemlidir. Ancak yapılan çalışmalarda öğrencilerin yaş ilerledikçe daha az merak ettikleri ve daha az sorguladıkları ifade edilmektedir (Doğan, Han Tosunoğlu, Özer & Akkan, 2020;İnel Ekici, 2017;Martin, 2003). Uluslararası sınavlarda başarılı olan ülkelerin genellikle sorgulama becerilerini geliştirmeye daha çok dikkat eden ve gündelik hayatla bilimi ilişkilendiren öğretim programlarına sahip ülkeler oldukları görülmüştür (Firman, Ertikanto & Abdurrahman, 2018).…”
Section: Introductionunclassified
“…It can be said that the results of the studies conducted with middle-schoolers (Işık, 2011;Katrancı & Şengül, 2020;Okumuş & Yetkil, 2020) are in parallel with the result of this study regarding the decrease in inquiry learning skills as the grade level increases. Doğan et al (2020) stated in their study that the development of understanding toward scientific inquiry starts in primary school years. In this direction, it can be said that the fact that there is no difference according to grade level shows that the education given to students in middle schools does not contribute to their inquiry learning skills.…”
Section: Resultsmentioning
confidence: 99%